Peru : First Review Under the Stand-By Arrangement and Requests for Modification of Performance Criterion and Waiver for Nonobservance of Performance Criterion. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
The staff report for the First Review Under the Stand-By Arrangement and Requests for Waiver of Performance Criterion and Waiver for Nonobservance of Performance Criterion highlights Peru's policy discussions and staff appraisal. A draft law was prepared with a view to establishing sanctions for noncompliance with the law's fiscal deficit target. Monetary policy continues to be managed prudently within the inflation-targeting framework. The central bank expects dollarization to gradually decline as a result of sound economic policies and strong bank supervision.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet